Exposure to uppercott induces hepatotoxicity in male albino wistar rats - Modo, Emmanuel; Uboh, Friday; Agiang, Margaret; Ewere, Efosa (International Journal of Scientific World, 2017)
Background: The use of herbicides and pesticides in agriculture and for public health purposes has led to harmful effects in many non-target species including man.Methods: In this study, the hepatic effect of exposure to cypermethrin and dimethoate mixture (uppercott) was investigated in male albino wistar rats. Forty five (45) male wistar albino rats were distributed into five (5) groups of nine (9) animals each. Groups 1 and 2 served as the normal control and oil control respectively, groups 3, 4 and 5 received 2.5%, 5% and 7.5% LD50 of uppercott orally for 28 days.Results: Results obtained revealed that uppercott exposure significantly (p<0.05) increased serum aspartate aminotransferase (AST) activity, alanine aminotransferase (ALT) activity and alkaline phosphatase (ALP) activity when the test groups were compared with control. Also, uppercott exposure raised serum bilirubin concentration slightly insignificantly compared to the control. Superoxide dismutase activity was significantly reduced across all test groups as compared with compared with control. Histology of liver tissues revealed patchy necrotic sessions in the liver tissues of the test experimental groups (2.5%, 5% and 7.5%).Conclusion: The results obtained from this study are strongly indicative of the hepatotoxic effect of uppercott pesticide and hence, caution during usage is advised.